Symbolic interaction and intercultural theatre performance dynamics in Uganda : the case of Makerere Universitys Intercultural Theatre Collaborations - Kagolobya, Richard (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2014.